Connective Tissue Growth Factor From Periosteal Tartrate Acid Phosphatase-Positive Monocytes Direct Skeletal Stem Cell Renewal and Fate During Bone Healing - Bai, Yun; Yu, Tao; Deng, Jiezhong; Yang, Yusheng; Tan, Jiulin; Dai, Qijie; Zhang, Zehua; Dong, Shiwu; Xu, Jianzhong (Frontiers in Cell and Developmental Biology, 2021)
The periosteum is critical for bone healing. Studies have shown that the periosteum contains periosteal stem cells (PSCs) with multidirectional differentiation potential and self-renewal ability. PSCs are activated in early fracture healing and are committed to the chondrocyte lineage, which is the basis of callus formation. However, the mechanism by which PSCs are activated and committed to chondrocytes in bone regeneration remains unclear. Here, we show that tartrate acid phosphatase (TRAP)-positive monocytes secrete CTGF to activate PSCs during bone regeneration. The loss function of TRAP-positive monocytes identifies their specific role during bone healing. Then, the secreted CTGF promotes endochondral ossification and activates PSCs in mouse bone fracture models. The secreted CTGF enhances PSC renewal by upregulating the expression of multiple pluripotent genes. CTGF upregulates c-Jun expression through αVβ5 integrin. Then, c-Jun transcription activates the transcription of the pluripotent genes Sox2, Oct4, and Nanog. Simultaneously, CTGF also activates the transcription and phosphorylation of Smad3 through αVβ5 integrin, which is the central gene in chondrogenesis. Our study indicates that TRAP-positive monocyte-derived CTGF promotes bone healing by activating PSCs and directing lineage commitment and that targeting PSCs may be an effective strategy for preventing bone non-union.